2017
DOI: 10.1093/nar/gkx969
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis and iron-dependency of ribosomal RNA hydroxylation

Abstract: Post-transcriptional modifications of ribosomal RNAs (rRNAs) are involved in ribosome biogenesis and fine-tuning of translation. 5-Hydroxycytidine (ho5C), a modification of unknown biogenesis and function, is present at position 2501 of Escherichia coli 23S rRNA. We conducted a genome-wide screen in E. coli to identify genes required for ho5C2501 formation, and found a previously-uncharacterized gene, ydcP (renamed rlhA), iron-sulfur cluster (isc) genes, and a series of genes responsible for prephenate biosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(76 citation statements)
references
References 90 publications
(102 reference statements)
8
68
0
Order By: Relevance
“…coli versus 18 copies in B. subtilis) (1). As recently described by Kimura et al (21) and shown in Fig. 2, E. coli contains four peptidase U32 genes as follows: rlhA (ydcP), yegQ, and a putative operon containing the two adjacent genes yhbU and yhbV.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…coli versus 18 copies in B. subtilis) (1). As recently described by Kimura et al (21) and shown in Fig. 2, E. coli contains four peptidase U32 genes as follows: rlhA (ydcP), yegQ, and a putative operon containing the two adjacent genes yhbU and yhbV.…”
Section: Resultsmentioning
confidence: 88%
“…2B, and also weak homology to Fe-S clustercontaining proteins in both bacteria and archaea. In addition, Kimura et al (21) published that the peptidase U32 gene rlhA was required for ho 5 C synthesis in E. coli rRNA. Thus, it was likely that one or both of these genes were required for ho 5 U synthesis in tRNA in B. subtilis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations